Sovereign credit ratings and their impact on recent financial crises - Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper discusses the role of the credit rating agencies during the recent financial crises. In particular, it examines whether the agencies can add to the dynamics of emerging market crises. Academics and investors often argue that sovereign credit ratings are responsible for pronounced boom-bust cycles in emerging-markets lending. Using a vector autoregressive system this paper examines how US dollar bond yield spreads and the short-term international liquidity position react to an unexpected sovereign credit rating change. Contrary to common belief and previous studies, the empirical results suggest that an abrupt downgrade does not necessarily intensify a financial crisis.
urn:nbn:de:hebis:30-9698
Keywords: C22; C51; G10; 330; Risk Management; Value at Risk; Density Forecasting; Predictive Likelihood